2020
DOI: 10.1016/j.jmoldx.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gene Expression Analysis on Cytology Smears Can Rule Out Malignancy in Follicular-Patterned Thyroid Tumors

Abstract: it.Patients with indeterminate thyroid nodules (Bethesda III and IV) are often treated with diagnostic lobectomy, which in most cases represents an overtreatment. A reliable rule-out molecular test could spare patients unnecessary surgery. Stained smears of 88 indeterminate thyroid nodules with histologic diagnosis of follicular-patterned tumors were selected: 34 follicular adenomas (FAs), 34 follicular variant papillary thyroid carcinomas (FVPTCs), and 20 noninvasive follicular neoplasms with papillarylike nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Gene expression profiling has been widely evaluated in thyroid cancer for biomarker discovery, especially for diagnostic purposes (14)(15)(16)(17). Transcriptomic-based studies have revealed predictors candidates of prognosis, including overexpression of MUC1 (18), MEDAG (19), and SPHK1 (20), and downexpression of FMO1 (21), and FOXF1 (22).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling has been widely evaluated in thyroid cancer for biomarker discovery, especially for diagnostic purposes (14)(15)(16)(17). Transcriptomic-based studies have revealed predictors candidates of prognosis, including overexpression of MUC1 (18), MEDAG (19), and SPHK1 (20), and downexpression of FMO1 (21), and FOXF1 (22).…”
Section: Introductionmentioning
confidence: 99%
“…Few previous studies were carried out on differential diagnosis of FTC and FA, most of which focused on improvements in diagnosis methods in cytology or pathology 6 , 7 , 36 . Our study exhibited a noninvasive, high-precision preoperative predicting system on follicular thyroid neoplasms for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…However, authors mostly focused on differential miRNA expression between malignant and benign tumors, without considering the presence of RAS mutations as a confounding factor [ 24 26 ]; on the contrary, several miRNAs are known to be specifically deregulated in BRAF mutant thyroid tumors compared to wild-type cases [ 27 , 28 ]. In previous studies from our group, we demonstrated that wild-type NIFTPs show a benign-like miRNA phenotype, while RAS -mutant NIFTPs show a malignant-like miRNA phenotype [ 29 , 30 ]; in detail, 12 miRNAs were significantly deregulated in mutant versus wild-type NIFTPs ( miR-221-5p , miR-221-3p , miR-222-3p , miR-146b-5p , miR-181a-3p , miR-28-5p , miR-363-3p , miR-342-3p , miR-1285-5p , miR-152-3p , miR-25-3p , miR-30e-3p ) [ 30 ]. Likewise, comparing RAS -negative and RAS -mutant FAs, herein we report 12 differentially expressed miRNAs, whose deregulation is likely related to RAS mutations ( miR-222-3p , miR-7-5p , miR-221-3p , miR-221-5p , miR-19a-3p , miR-135a-5p , miR-146b-5p , let-7a-5p , miR-92a-3p , miR-142-3p , miR-296-5p , miR-26a-5p ).…”
Section: Discussionmentioning
confidence: 99%